747 Long-term effects of pharmacological treatment in patients with takotsubo syndrome with or without hypertension: a report from the takotsubo Italian network. (8th December 2021) - Silverio, Angelo; Migliarino, Serena; Iuliano, Giuseppe; Bossone, Eduardo; Bellino, Michele; Provenza, Gennaro; Cameli, Matteo; Innelli, Pasquale; Zito, Concetta; Novo, Giuseppina; Antonini-Canterin, Francesco; Rigo, Fausto; et al.
Abstract: Aims: Hypertension (HT) is one of the most frequent comorbidities reported in patients with Takotsubo syndrome (TTS). However, the clinical outcome as well as the effect of pharmacological treatment on long-term follow-up have never been investigated in this cohort. To investigate the impact of the pharmacological treatment with beta-blocker (BB) and/or renin–angiotensin–aldosterone system inhibitor (RAASi) on long-term outcome of TTS patients with and without HT. Methods and results: This study included TTS patients prospectively included in the Takotsubo Italian Network register from January 2007 to December 2018. The study population was divided in two groups according to the presence or not of HT. The effect of BB and RAASi at discharge was evaluated in these groups. The primary outcome was the composite of all-cause death and TTS recurrence; secondary outcomes were the single components of the primary outcome. The propensity score weighting technique was employed to account for potential selection bias in treatment assignment at discharge. The study population included 825 patients [median age 72 (63–78) years; 8.1% were males]; 525 (63.6%) patients had history of HT and 300 (36.4%) patients did not. At median follow-up of 24.0 months (11.0–38.0), the primary outcome occurred in 102 patients (12.4%); all-cause death and TTS recurrence were reported in 76 (9.2%) and 33 (4.0%), respectively. There were no differences in terms of the primary outcome (adjusted HR: 1.082; 95% CI: 0.689–1.700; P = 0.733), all-cause death (adjusted HR: 1.214; 95% CI: 0.706–2.089; P = 0.483) and TTS recurrence (adjusted HR: 0.795; 95% CI: 0.373–1.694; P = 0.552) between patients with vs. without HT. Among patients with HT, those receiving BB at discharge showed a significantly lower risk of the primary outcome (adjusted HR: 0.375; 95% CI: 0.228–0.617; P < 0.001) compared with patients not receiving BB. There was also a significantly lower risk of all-cause death (adjusted HR: 0.381; 95% CI: 0.217–0.666; P < 0.001) and TTS recurrence (adjusted HR: 0.393; 95% CI: 0.155–0.998; P = 0.049) in patients treated with BB. Among patients without HT, there was no significant association of BB treatment with any of the study outcomes. RAASi treatment showed no significant effect on the primary and secondary outcomes. These results were consistent between patients with and without HT. Conclusions: TTS patients with HT patients experienced a survival benefit from BB treatment in terms of both all-cause death and TTS recurrence; this effect was not confirmed in patients without HT. Conversely, RAASi did not affect long-term outcome, independently from the coexistence of HT. Albeit hypothesis-generating, a such evidence supports a tailored pharmacological therapy after discharge in TTS patients taking into account the coexistence of HT.